The Changing Roles Of Administrative Professionals In The Office Of The Future - Siregar, Yakin Bakhtiar (Jurnal Administrasi dan Kesekretarisan, 2018)
One trend in modern business is the changing nature of administrative work. Currently in business of all sizes, many managers do work on their own computer systems, where in the past the work was handled by the secretary. As this trend continues, little by little administrative assistants are required to master more office and information specialists. It is up to the workers to create a place for themselves in this changing world. Learning new skills and improving old skills is the best professional warranty gained. The most important qualities needed by Administrative Professionals are acts as a liaison, adaptability, punctuality, dependability, ability to learn, willingness to follow instructions, loyalty, and confidentiality. While the strategy to face office changes in the future can be done by handling change, handling feedback and criticism, staying organized, thingking skills, knowing when to act, your professional image, communication skills, teamwork skills, professional organizations, and bussines etiquette. Another important aspect for administrative assistants is how to evaluate performance to find out how far they have performed the tasks that the company is delivering in accordance with the expected planning and targets. Assessment of administrative assistant performance consists of 6 categories namely effectiveness, efficiency, quality, accuracy, productivity, and safety and security.Salah satu tren dalam bisnis modern adalah perubahan sifat pekerjaan administratif. Saat ini dalam bisnis dari semua ukuran, banyak manajer melakukan pekerjaan pada sistem komputer mereka sendiri, dimana di masa lalu pekerjaa tersebut ditangani oleh sekretaris. Seiring tren ini berlanjut, sedikit demi sedikit administrative assistant dituntut lebih banyak menguasai spesialis perkantoran dan informasi. Terserah para pekerja untuk menciptakan tempat bagi dirinya sendiri di dunia yang sedang berubah ini. Mempelajari keterampilan baru dan memperbaiki kemampuan lama adalah garansi profesional yang terbaik yang didapatkan. Kualitas paling penting yang dibutuhkan oleh Administrative Professional adalah acts as a liaison, adaptability, punctuality, dependability, ability to learn, willingness to follow instructions, loyalty, dan confidentiality. Sedangkan strategi untuk menghadapi perubahan kantor di masa depan dapat dilakukan dengan cara handling change, handling feedback and criticism, staying organized, thingking skills, knowing when to act, your professional image, communication skills, teamwork skills, Professional organizations, dan bussines etiquette.Â  Aspek lain yang penting bagi administrative assistant adalah bagaimana mengevaluasi kinerja untuk mengetahui seberapa jauh telah melakukan tugas-tugas yang diberikan perusahaan sesuai dengan perencanaan dan target yang diharapkan.Â  Penilaian kinerja administrative assistant terdiri dari 6 kategori yaitu efektifitas, efisiensi, kualitas, ketepatan, produktivitas, serta keselamatan dan keamanan.Â